1983
DOI: 10.1080/03015521.1983.10427722
|View full text |Cite
|
Sign up to set email alerts
|

Performance of 4 white clover populations in monoculture and with ryegrass under grazing

Abstract: Herbage accumulation and botanical composition of pastures containing 4 morphologically-contrasting white clovers (Kent wild white, Southland uncertified, 'Grasslands Huia', and 'Grasslands Pitau') are described. The clovers were grown in monoculture and in association with either 'Grasslands Ruanui' or 'Nui' perennial ryegrass under grazing frequencies of 4 and 6 weeks. Clover production in monoculture and mixtures was least from the small-leaved Kent, intermediate for medium-leaved clovers, and greatest from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Thetotal annual pasture production wassimilar for all clover-grass swards as found in other studies (Widdup & Turner 1983;van den Bosch et aI. 1986).…”
Section: Discussionsupporting
confidence: 66%
“…Thetotal annual pasture production wassimilar for all clover-grass swards as found in other studies (Widdup & Turner 1983;van den Bosch et aI. 1986).…”
Section: Discussionsupporting
confidence: 66%
“…A similar effect was measured in a mowing experiment in the United Kingdom (Camlin 1981) and in a grazing experiment in Southland (Widdup & Turner 1983). This effect reflects differences in competitiveness between white clover and the associated ryegrass, and is probably due mainly to the greater light interception ability of the erect-growing largeleaved cultivars (Aran and Kopu) in competition with ryegrass (Harris 1987).…”
mentioning
confidence: 58%
“…Several New Zealand studies have shown greater production by large-leaved cultivars of white clover grown in mixed swards with no N fertiliser application (Widdup & Turner 1983;van den Bosch et al 1986;Ledgard et al 1990). Only one recent experiment in New Zealand has compared cultivars under different N regimes.…”
Section: Introductionmentioning
confidence: 99%
“…These include: a shortage of soil N ); association with a grass (Widdup & Turner 1983); a high rate of seeding of an associated grass (McDonald & Cullen 1973); a very hard grazing (Weeda et al 1969;During & Weeda 1974); too short an interval between grazings ; and both set stocking and rotational grazing with sheep (Williams et al 1982). In the latter experiment, Pitau was only superior to Huia when grazed rotationally by cattle.…”
Section: Leaf Size and Competitionmentioning
confidence: 99%